2001
DOI: 10.1038/sj.bmt.1702752
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo generation of cytotoxic T lymphocytes specific for one or two distinct viruses for the prophylaxis of patients receiving an allogeneic bone marrow transplant

Abstract: Summary:Human adenovirus (AdV) infection and EBV-lymphoproliferative disease (LPD) are serious complications following allogeneic stem cell transplantation. In the healthy individual these viruses cause minor, self-limiting diseases but in the immunocompromised patient they are responsible for significant morbidity and mortality. The limitations of anti-viral drugs and a better understanding of the cellular immune response to viral pathogens have prompted interest in developing adoptive immunotherapy for trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 38 publications
1
24
0
1
Order By: Relevance
“…The reduction of immunosuppression, combined with antiviral therapy initiated as early as possible after the adenovirus infection, remains the mainstay of therapy (1,8,9,22). Alternatively, there may be a therapeutic benefit with adenovirus-specific T cells, similar to that described for Epstein-Barr virus and cytomegalovirus (46,50). Due to extensive cross-reactivity of adenovirus-specific T cells across serotypes, this approach may be feasible (20,51).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of immunosuppression, combined with antiviral therapy initiated as early as possible after the adenovirus infection, remains the mainstay of therapy (1,8,9,22). Alternatively, there may be a therapeutic benefit with adenovirus-specific T cells, similar to that described for Epstein-Barr virus and cytomegalovirus (46,50). Due to extensive cross-reactivity of adenovirus-specific T cells across serotypes, this approach may be feasible (20,51).…”
Section: Discussionmentioning
confidence: 99%
“…Various research groups are currently investigating the role of CD4 þ and CD8 þ T cells in the cellular immune response to HAdV. 23,[25][26][27] Together with a more detailed analysis of the origin of the infectious HAdV in the setting of allogeneic SCT and of the HAdV type(s) infecting a patient, this research will certainly enhance our knowledge of the interaction between HAdV and the immune system. This will be of benefit not only for recipients of stem cell grafts but also for recipients of solid organ transplants and other immunocompromised patients in which HAdV infection may have serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Flomenberg et al demonstrated adenovirus-specific cellular immunity in healthy donors, 25,26 and others have also reported the generation of adenovirus-specific CTLs. 27,28 Unlike neutralizing antibodies, adenovirus CTLs may not be serotype restricted, suggesting that serotype variation might not be a stumbling block for developing adoptive cellular therapy. 29 We are currently investigating the kinetics of adenovirusspecific T-cell recovery following an allograft and whether this is predictive of the acquisition and outcome of adenovirus infections.…”
Section: Discussionmentioning
confidence: 99%